Hubungan Pola EKG Infark dan Iskemik dengan Derajat Stenosis Berdasarkan Gensini Score - Rohman, Fatuh; Abduh, Saugi; Sumarawati, Titiek (Jurnal Kesehatan Andalas, 2025)
Myocardial infarction and ischemia are progressive manifestations of coronary heart disease due to coronary artery stenosis. ECG examination can be an initial tool for detecting infarction and ischemia. However, it has relatively low sensitivity and specificity in detecting arterial stenosis. Objective: To determine the relationship between infarction and ischemic ECG patterns with the degree of stenosis based on the Gensini score and risk factors that influence the degree of stenosis. Methods: This observational analytical study employed a cross-sectional design, utilizing secondary data from medical records at RSI Sultan Agung Semarang from January 2018 to December 2023. The degree of stenosis was calculated using the Gensini score method. Results: A total of 500 patient data were analyzed using a Chi-square test to examine ischemic and infarction ECG patterns in relation to the degree of stenosis, yielding a p-value of 0.001 and a contingency coefficient of 0.15. Conclusion: A significant relationship was found between infarction and ischemic ECG patterns, as well as the degree of stenosis, based on the Gensini score, with a very weak correlation strength. Keywords: degree of stenosis, Gensini score, infarction, ischemic